A calcium self-grown lignin-based carbon capture electrospun nanofiber membrane and preparation method thereof
By combining electrospinning and carbonization processes, calcium self-grown lignin-based carbon capture electrospun nanofiber membranes are prepared using lignin and calcium sources, solving the efficiency and stability of existing carbon nanofiber membranes in CO2 capture. , achieving efficient and simple carbon capture effect.
Patent Information
- Application Number
- CN202410925571.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-07-11
AI Technical Summary
The existing carbon nanofiber membranes have problems such as limited adsorption capacity, low capture efficiency and poor stability in CO2 capture, and the existing modification methods are complex and not suitable for large-scale promotion.
Through electrospinning technology and carbonization process, lignin is used as a basic raw material, and calcium source is added during the preparation process to construct a calcium-self-grown lignin-based carbon capture electrospun nanofiber membrane.
It has achieved efficient CO2 capture, with the advantages of large specific surface area, excellent flexibility, uniform calcium source distribution, excellent stability and simple preparation process, and is suitable for large-scale industrial promotion.
Smart Images

Figure CN118685922B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomass resource utilization and industrial source CO2 capture, and in particular relates to a calcium self-growing lignin-based carbon capture electrospun nanofiber membrane and a preparation method thereof. Background Art
[0002] Excessive global CO2 emissions have led to increasingly serious environmental pollution. Currently, carbon capture, storage and utilization technology is considered to be a very promising negative carbon solution technology. Through this technology, a large amount of carbon dioxide can be efficiently captured from industrial sources and converted into chemicals, materials or fuels, thereby achieving efficient recovery and utilization of CO2. In carbon capture technology, carbon capture agents play a vital role.
[0003] Among many carbon capture agents, carbon nanofiber membranes have shown broad application prospects in the field of carbon capture due to their efficient CO2 separation capabilities, convenient installation process, and non-toxic and non-corrosive properties. However, the capture of CO2 by relying solely on the physical adsorption behavior of carbon nanofiber membranes has problems such as limited adsorption capacity, low capture efficiency, and poor stability. The existing modified carbon nanofiber membranes and preparation methods still have the following problems, such as:
[0004] CN115945023A discloses a method for preparing a carbon nanofiber membrane by using silkworm cocoons as raw materials, firstly treating the silkworm cocoons under high pressure reaction conditions to obtain solid silk fibroin, and then electrospinning the solid fibroin with polyvinyl alcohol. Although the carbon nanofiber membrane prepared by this method has a good carbon capture effect, the silk processing process is relatively complicated and requires specific pressure conditions. These factors are not conducive to the large-scale promotion and application of this technology.
[0005] CN116651417A discloses an amine-based hollow fiber membrane for carbon dioxide capture, wherein the amine compounds involved include diethylenetriamine, triethylenetetramine, polyvinyleneamine, etc. In the preparation process of the membrane, succinaldehyde, adipic acid, p-dibenzaldehyde, etc. are also used as cross-linking agents to enhance the stability of the membrane. The method uses a wide variety of solvents, which increases the complexity of the preparation process.
[0006] CN109647359A discloses a method for preparing an ionic liquid functionalized polyacrylonitrile nanofiber membrane and its application in the field of solid phase extraction. The patent achieves the separation and enrichment of target substances in complex matrix samples. However, the high cost of ionic liquids and the difficulty in recovering solvents remain to be solved.
[0007] Therefore, there is an urgent need to provide a carbon capture electrospun nanofiber membrane with abundant raw material sources, simple preparation method, and high carbon adsorption performance. Summary of the invention
[0008] In order to solve the above technical problems, the present invention proposes a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane and a preparation method thereof.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] One of the technical solutions of the present invention:
[0011] A method for preparing a calcium self-growing lignin-based carbon capture electrospun nanofiber membrane comprises mixing a calcium source, lignin and a spinning aid solution, and performing electrostatic spinning and carbonization treatment to prepare a calcium self-growing lignin-based carbon capture electrospun nanofiber membrane.
[0012] Beneficial effects: The present invention combines electrospinning technology with carbonization process, uses lignin as the basic raw material, successfully prepares lignin-based carbon nanofiber membrane, and creatively adds calcium source in the preparation process to construct a calcium self-growing lignin-based electrospun nanofiber membrane.
[0013] The principle involved is: the present invention uses lignin, which is widely present in nature, as raw material to synthesize high-performance carbon dioxide capture materials through electrospinning technology, which effectively solves the problem of low carbon dioxide capture efficiency while realizing high-value utilization of lignin; while constructing a high-performance fiber pore structure to enhance the effective adsorption of carbon dioxide, the sulfur-containing properties of lignin are used to realize the self-growth process of calcium source on its surface, thereby enhancing its chemical adsorption effect, and having a strong coupling effect of physical adsorption of lignin-based carbon nanofiber membrane and chemical adsorption of self-grown calcium source on the fiber surface, ultimately achieving the ideal effect of carbon dioxide capture.
[0014] Preferably, the preparation method comprises the following steps:
[0015] The lignin raw material is placed in a constant temperature oven to remove moisture;
[0016] The high molecular polymer is mixed with the polar solvent, and after sufficient stirring and dissolution, a uniform and stable spinning aid solution is obtained;
[0017] The spinning aid solution is mixed with lignin and a calcium source, and placed in a constant temperature water bath for water bath treatment to obtain a uniform spinning precursor solution;
[0018] The spinning precursor solution is placed in an electrospinning device to perform an electrospinning process to prepare a calcium-containing lignin-based nanofiber membrane, and then the prepared fiber membrane is placed in an oven for drying to remove residual solvent and moisture;
[0019] The dried calcium-containing lignin-based nanofiber membrane is placed in a tubular heater for activation treatment;
[0020] After the activation treatment process is completed, the calcium source is self-grown on the fiber membrane surface and carbonized, and then naturally cooled to room temperature to obtain a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane.
[0021] Preferably, the lignin content in the spinning precursor solution is 5-20wt%; and the added amount of the calcium source is 5-60% of the lignin quality.
[0022] Beneficial effects: The range of lignin and calcium source additions defined in the present invention is the optimal content range; among them, regarding the lignin content, if the lignin content in the spinning precursor solution is too low, it is not conducive to the preparation of carbon nanofiber membranes; if the lignin content is too high, electrospinning nanofiber membranes cannot be prepared. Regarding the calcium source content, if the calcium source addition content is too small, the chemical adsorption effect of the nanofiber membrane is weak; if the calcium source addition content is too large, it is easy to cause uneven distribution of calcium-containing particles on the fiber surface, weakening the carbon capture effect of the fiber membrane.
[0023] Preferably, the stirring rate is 100-600 rpm.
[0024] Preferably, the water bath treatment is as follows: the water bath temperature is 50 to 80° C., and the water bath time is 2 to 6 hours.
[0025] Preferably, the calcium source includes one or more of calcium chloride dihydrate, calcium formate, calcium acetate, calcium nitrate tetrahydrate and calcium hydroxide.
[0026] Preferably, the spinning aid solution is obtained by uniformly mixing a high molecular polymer and a polar solvent in a mass volume ratio of 1 g: (5-20) mL.
[0027] Beneficial effect: The present invention limits the dosage ratio of high molecular polymer and polar solvent. If it exceeds or decreases this mass volume range, it will lead to difficulties in the electrospinning process, inability to stably form filaments, and it is difficult to ensure the successful preparation of lignin-based carbon capture electrospun fiber membranes.
[0028] Further, the high molecular polymer includes one or more of polyacrylonitrile, polyacrylonitrile copolymer, polyether sulfone, polylactic acid, polyvinyl alcohol, polyoxyethylene, polyvinylidene fluoride and polyvinyl pyrrolidone;
[0029] The polar solvent includes one or more of N,N dimethylformamide, N,N dimethylacetamide, acetone, dichloromethane, dimethyl sulfoxide, and acetic acid.
[0030] Beneficial effect: Within the range of the above-mentioned high molecular polymer and polar solvent specified in the present invention, it can be ensured that lignin and the spinning aid solution have good dispersion compatibility and conductivity. The excellent dispersion compatibility and conductivity are sufficient to ensure the electrospinning process, thereby obtaining continuous and uniform lignin-based electrospun fibers.
[0031] Preferably, the parameters in the electrospinning process are:
[0032] The distance between the syringe needle and the receiving device is controlled to be 15 to 20 cm, the applied voltage is 10 kV to 25 kV, the advancement rate is 0.02 to 1.0 mm / min, and the receiver rotation speed is 100 to 500 rpm.
[0033] Preferably, the parameters in the activation treatment process are: in an air atmosphere, the temperature is increased from room temperature to 100-300° C. at a heating rate of 1-3° C. / min, and maintained at 100-300° C. for 1-5 hours.
[0034] Beneficial effects: The present invention defines the range of parameters such as the distance between the syringe needle and the receiving device, the applied voltage, the propulsion rate, and the receiver rotation speed. Appropriate electrospinning parameters ensure the successful preparation of lignin-based electrospun fibers and excellent physical and chemical properties of the fibers. In addition, the present invention defines parameters such as the heating rate, activation temperature, and holding time of the activation treatment process to retain the pore structure of the prepared electrospun fibers and avoid the collapse of the fiber pores caused by the subsequent carbonization process.
[0035] Preferably, the carbonization process is carried out in a mixed gas atmosphere of carbon monoxide and nitrogen;
[0036] The carbon monoxide accounts for 5-30% of the mixed gas flow rate, and the flow rate of the mixed gas is 80-260 mL / min.
[0037] Beneficial effects: The present invention limits the type, mixing ratio and flow rate of the gas atmosphere during the carbonization treatment. On the one hand, within this range, the fiber can be stably carbonized and its excellent pore structure can be maintained; on the other hand, outside the above range, the lignin-based electrospun fibers are prone to fiber breakage and other problems during the carbonization process, affecting the stability of the fibers.
[0038] Preferably, the temperature during the carbonization process is:
[0039] Raise the temperature from room temperature to 600-900°C and maintain at 600-900°C for 1-3 hours.
[0040] Furthermore, the heating rate is 3-10°C / min.
[0041] Beneficial effects: The present invention limits the carbonization temperature, carbonization time and heating rate of the carbonization process. Carbon nanofibers with excellent physical and chemical properties cannot be obtained outside the above range. For example, if the carbonization temperature is too low, it is not conducive to the complete carbonization of the fiber, and if the temperature is too high, the fiber pore structure will be destroyed; if the heating rate is too high, it will easily cause uneven carbonization temperature inside and outside the fiber, which is not conducive to the formation of carbonized fiber pores.
[0042] The second technical solution of the present invention:
[0043] A calcium self-grown lignin-based carbon capture electrospun nanofiber membrane is prepared by the above preparation method. Its specific surface area is 79.62m 2 / g.
[0044] Beneficial effects: The calcium self-grown lignin-based carbon capture electrospun nanofiber membrane prepared by the present invention has the advantages of large specific surface area, excellent flexibility, uniform distribution of calcium source, excellent stability and simple preparation process. It has excellent performance in CO2 capture performance and has great application potential and broad market prospects in the field of industrial carbon capture.
[0045] Compared with the prior art, the present invention has the following advantages and technical effects:
[0046] The present invention proposes a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane and a preparation method thereof; lignin is successfully converted into a high-performance carbon capture material, realizing the organic integration of high-value utilization of lignin and carbon capture function; and a calcium source is added during the preparation process, effectively realizing the physical adsorption and chemical adsorption coupling of the carbon capture nanofiber membrane material, so that it has high-efficiency carbon adsorption performance.
[0047] While realizing the resource utilization, high-value disposal and utilization of lignin, the present invention effectively solves the problem of carbon dioxide capture from industrial sources, and strongly promotes the high-quality completion of the country's "dual carbon" strategic goals.
[0048] The preparation process of the present invention is simple and fast, abandoning the traditional preparation process of using strong acid and strong alkali to obtain excellent pore structure, which is green and environmentally friendly with high safety factor, and suitable for large-scale industrial promotion and application. At the same time, lignin has a wide range of sources, low price and easy to obtain, which effectively promotes energy, electricity, chemical and other emission reduction and carbon reduction enterprises to achieve the goal of reducing costs and increasing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0050] Figure 1 This is the X-ray diffraction pattern of the calcium self-grown lignin-based carbon capture electrospun nanofiber membrane prepared in Example 1 of the present invention;
[0051] Figure 2 This is a microscopic morphology of the calcium self-grown lignin-based carbon capture electrospun nanofiber membrane prepared in Example 1 of the present invention;
[0052] Figure 3This is a physical picture of the calcium self-grown lignin-based carbon capture electrospun nanofiber membrane prepared in Example 1 of the present invention;
[0053] Figure 4 This is the pore size distribution diagram of the calcium self-grown lignin-based carbon capture electrospun nanofiber membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0054] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0055] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0056] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0057] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0058] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0059] The present invention provides a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane and a preparation method thereof, comprising the following steps:
[0060] The lignin raw material is placed in a constant temperature oven to remove moisture;
[0061] The high molecular polymer and the polar solvent are mixed in a certain proportion, and after sufficient stirring and dissolution, a uniform and stable spinning aid solution is obtained;
[0062] The spinning aid solution is mixed with lignin and a calcium source, and placed in a constant temperature water bath for water bath treatment to obtain a uniform spinning precursor solution;
[0063] The spinning precursor solution is placed in an electrospinning device to carry out an electrospinning process to prepare a calcium-containing lignin-based nanofiber membrane, and then the prepared fiber membrane is placed in an oven for drying to remove residual solvent and moisture;
[0064] The dried calcium-containing lignin-based nanofiber membrane is placed in a tubular heater for activation treatment;
[0065] After the activation process is completed, the temperature and atmosphere conditions are changed to carry out the self-growth process of the calcium source on the fiber membrane surface and the carbonization process. After it is naturally cooled to room temperature, a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane can be obtained.
[0066] In some preferred embodiments, the lignin includes one or more of hydrolyzed lignin, alkaline lignin, dealkalized lignin, acetic acid lignin, sulfonated lignin and black liquor lignin.
[0067] In some preferred embodiments, the high molecular polymer includes one or more of polyacrylonitrile, polyacrylonitrile copolymer, polyethersulfone, polylactic acid, polyvinyl alcohol, polyethylene oxide, polyvinylidene fluoride, and polyvinyl pyrrolidone.
[0068] In some preferred embodiments, the polar solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, acetone, dichloromethane, dimethyl sulfoxide, and acetic acid.
[0069] In some preferred embodiments, the mass volume ratio of the high molecular weight polymer to the polar solvent is 1 g: (5-20) mL.
[0070] In some preferred embodiments, the stirring rate is 100-600 rpm.
[0071] In some preferred embodiments, the water bath temperature is 50-80° C., and the water bath time is 2-6 hours.
[0072] In some preferred embodiments, the lignin content in the spinning precursor solution is 5-20 wt %, and the calcium source content is 5-60% of the lignin mass.
[0073] In some preferred embodiments, the calcium source includes one or more of calcium chloride dihydrate, calcium formate, calcium acetate, calcium nitrate tetrahydrate, and calcium hydroxide.
[0074] In some preferred embodiments, during the spinning process: the distance between the syringe needle and the receiving device is controlled to be 15-20 cm, the applied voltage is 10 kV-25 kV, the propulsion rate is 0.02-1.0 mm / min, and the receiver rotation speed is 100-500 rpm.
[0075] In some preferred embodiments, the activation treatment atmosphere is an air atmosphere, and the temperature is increased from room temperature to 100-300° C. at a heating rate of 1-3° C. / min and maintained for 1-5 hours.
[0076] In some preferred embodiments, the atmosphere of the calcium source self-growth process and carbonization treatment process on the fiber membrane surface is a mixture of carbon monoxide and nitrogen, wherein carbon monoxide accounts for 5-30% of the total mixed gas flow rate, the mixed gas flow rate is 80-260 mL / min, the heating rate is 3-10°C / min, the temperature range is from room temperature to 600-900°C, and is maintained for 1-3 hours.
[0077] All raw materials used in the examples of the present invention are commercially available.
[0078] Unless otherwise specified, the “parts” used in the embodiments of the present invention are “parts by weight”.
[0079] The technical solution of the present invention is further illustrated by the following embodiments.
[0080] Example 1
[0081] A method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane for carbon dioxide capture, specifically comprising the following steps:
[0082] 1) Dry the dealkalized lignin in an oven at 80°C for 2 hours for later use;
[0083] 2) Dissolve 1.0 g of polyacrylonitrile in 10 mL of N,N-dimethylformamide and stir at a constant temperature of 60° C. for 8 h to obtain a uniform and stable spinning aid solution;
[0084] 3) adding 1.0 g of dried dealkalized lignin to the above spinning aid solution, stirring for 4 h at a water bath temperature of 60° C. and a stirring speed of 100 rpm, and adding 0.4 g of calcium nitrate tetrahydrate to the mixed solution under stirring to obtain a spinning precursor solution;
[0085] 4) injecting the spinning precursor solution into a 10 mL syringe, and preparing a calcium-containing lignin-based nanofiber membrane under the spinning parameter conditions of setting the syringe propulsion speed to 0.03 mm / min, the receiver rotation speed to 200 rpm, the distance between the syringe needle and the receiving device to 16 cm, and the voltage to 15 kV;
[0086] 5) drying the calcium-containing lignin-based nanofiber membrane obtained by spinning in an oven at 80° C. for 12 hours to remove the residual solvent and obtain a dry carbon fiber precursor material;
[0087] 6) placing the dried calcium-containing lignin-based nanofiber membrane in a heater and activating it in an air atmosphere, gradually heating it from room temperature to 220° C. at a heating rate of 1° C. / min, and keeping the temperature constant for 2 h, and then cooling it to room temperature;
[0088] 7) After the activation is completed, the reaction conditions are changed, and a mixed atmosphere of nitrogen and carbon monoxide is selected to further carry out the self-growth process of the calcium source on the fiber membrane surface and carbonization treatment, wherein the carbon monoxide gas flow rate is 10 mL / min, and the temperature is increased to 800°C at a heating rate of 5°C / min, and the total gas flow rate is maintained at 100 mL / min. After the constant temperature is maintained for 1 hour, it is naturally cooled to room temperature, and finally a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane is obtained.
[0089] The obtained calcium self-grown lignin-based carbon capture electrospun nanofiber membrane was tested for carbon dioxide adsorption performance. The sample was placed in a tubular furnace and heated to 500°C at a rate of 10°C / min under nitrogen conditions. It was pretreated at this temperature for 3 hours to completely remove excess moisture and gas to ensure the accuracy of the test results; the carbon dioxide adsorption capacity was 2.33mmol / g when the adsorption was carried out under the conditions of adsorption temperature of 140°C, adsorption time of 90min, nitrogen and carbon dioxide gas flow rates of 200mL / min and 3mL / min respectively.
[0090] Example 2
[0091] A method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane for carbon dioxide capture, specifically comprising the following steps:
[0092] 1) Dry the hydrolyzed lignin in an oven at 80°C for 2 hours for later use;
[0093] 2) Dissolve 1.0 g of polyvinyl alcohol in 10 mL of dimethyl sulfoxide and stir at a constant temperature of 60° C. for 8 h to obtain a uniform and stable spinning aid solution;
[0094] 3) adding 1.0 g of dried hydrolyzed lignin to the above spinning aid solution, stirring for 4 h at a water bath temperature of 60° C. and a stirring speed of 100 rpm, and adding 0.2 g of calcium chloride dihydrate to the mixed solution to obtain a spinning precursor solution;
[0095] 4) injecting the spinning precursor solution into a 10 mL syringe, and preparing a calcium-containing lignin-based nanofiber membrane under the spinning parameter conditions of setting the syringe propulsion speed to 0.03 mm / min, the receiver rotation speed to 200 rpm, the distance between the syringe needle and the receiving device to 16 cm, and the voltage to 15 kV;
[0096] 5) drying the calcium-containing lignin-based nanofiber membrane obtained by spinning in an oven at 80° C. for 12 hours to remove the residual solvent and obtain a dry carbon fiber precursor material;
[0097] 6) placing the dried calcium-containing lignin-based nanofiber membrane in a heater and activating it in an air atmosphere, gradually heating it from room temperature to 220° C. at a heating rate of 1° C. / min, and keeping the temperature constant for 2 h, and then cooling it to room temperature;
[0098] 7) After the activation is completed, the reaction conditions are changed, and a mixed atmosphere of nitrogen and carbon monoxide is selected to further carry out the self-growth process of the calcium source on the fiber membrane surface and carbonization treatment, wherein the carbon monoxide gas flow rate is 10 mL / min, and the temperature is increased to 800°C at a heating rate of 5°C / min, and the total gas flow rate is maintained at 100 mL / min. After the constant temperature is maintained for 1 hour, it is naturally cooled to room temperature, and finally a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane is obtained.
[0099] The obtained calcium self-grown lignin-based carbon capture electrospun nanofiber membrane was tested for carbon dioxide adsorption performance. The sample was placed in a tubular furnace and heated to 500°C at a rate of 10°C / min under nitrogen conditions. It was pretreated at this temperature for 3 hours to completely remove excess moisture and gas to ensure the accuracy of the test results; the carbon dioxide adsorption capacity was 2.24mmol / g when the adsorption was performed at a set adsorption temperature of 140°C, an adsorption time of 90min, and nitrogen and carbon dioxide gas flow rates of 200mL / min and 3mL / min respectively.
[0100] Example 3
[0101] A method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane for carbon dioxide capture, specifically comprising the following steps:
[0102] 1) Dry the sulfonated lignin in an oven at 80°C for 2 hours for later use;
[0103] 2) dissolving 1.0 g of polyvinyl pyrrolidone in 10 mL of dichloromethane / N,N-dimethylacetamide (mass ratio: 10:1), and stirring at a constant temperature of 60° C. for 8 h to obtain a uniform and stable spinning aid solution;
[0104] 3) adding 1.0 g of dried sulfonated lignin to the above spinning aid solution, stirring for 4 h at a water bath temperature of 60° C. and a stirring speed of 100 rpm, and adding 0.4 g of calcium nitrate tetrahydrate to the mixed solution to obtain a spinning precursor solution;
[0105] 4) injecting the spinning precursor solution into a 10 mL syringe, and preparing a calcium-containing lignin-based nanofiber membrane under the spinning parameter conditions of setting the syringe propulsion speed to 0.03 mm / min, the receiver rotation speed to 200 rpm, the distance between the syringe needle and the receiving device to 16 cm, and the voltage to 15 kV;
[0106] 5) drying the calcium-containing lignin-based nanofiber membrane obtained by spinning in an oven at 80° C. for 12 hours to remove the residual solvent and obtain a dry carbon fiber precursor material;
[0107] 6) placing the dried calcium-containing lignin-based nanofiber membrane in a heater and activating it in an air atmosphere, gradually heating it from room temperature to 220° C. at a heating rate of 1° C. / min, and keeping the temperature constant for 2 h, and then cooling it to room temperature;
[0108] 7) After the activation is completed, the reaction conditions are changed, and a mixed atmosphere of nitrogen and carbon monoxide is selected to further carry out the self-growth process of the calcium source on the fiber membrane surface and carbonization treatment, wherein the carbon monoxide gas flow rate is 10 mL / min, and the temperature is increased to 800°C at a heating rate of 5°C / min, and the total gas flow rate is maintained at 100 mL / min. After the constant temperature is maintained for 1 hour, it is naturally cooled to room temperature, and finally a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane is obtained.
[0109] The obtained calcium self-grown lignin-based carbon capture electrospun nanofiber membrane was tested for carbon dioxide adsorption performance. The sample was placed in a tubular furnace and heated to 500°C at a rate of 10°C / min under nitrogen conditions. It was pretreated at this temperature for 3 hours to completely remove excess moisture and gas to ensure the accuracy of the test results; the carbon dioxide adsorption amount was 2.09mmol / g when the adsorption temperature was set to 140°C, the adsorption time was 90min, and the nitrogen and carbon dioxide gas flow rates were 200mL / min and 3mL / min respectively.
[0110] Example 4
[0111] A method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane for carbon dioxide capture, specifically comprising the following steps:
[0112] 1) Dry the acetic acid lignin in an oven at 80°C for 2 hours for later use;
[0113] 2) Dissolve 1.0 g of polyvinylidene fluoride in 10 mL of dimethyl sulfoxide and stir at a constant temperature of 60° C. for 8 h to obtain a uniform and stable spinning aid solution;
[0114] 3) adding 1.0 g of dried acetic acid lignin to the above spinning aid solution, stirring for 4 h at a water bath temperature of 60° C. and a stirring speed of 100 rpm, and adding 0.4 g of calcium acetate to the mixed solution to obtain a spinning precursor solution;
[0115] 4) injecting the spinning precursor solution into a 10 mL syringe, and preparing a calcium-containing lignin-based nanofiber membrane under the spinning parameter conditions of setting the syringe propulsion speed to 0.03 mm / min, the receiver rotation speed to 200 rpm, the distance between the syringe needle and the receiving device to 16 cm, and the voltage to 15 kV;
[0116] 5) drying the calcium-containing lignin-based nanofiber membrane obtained by spinning in an oven at 80° C. for 12 hours to remove the residual solvent and obtain a dry carbon fiber precursor material;
[0117] 6) placing the dried calcium-containing lignin-based nanofiber membrane in a heater and activating it in an air atmosphere, gradually heating it from room temperature to 220° C. at a heating rate of 1° C. / min, and keeping the temperature constant for 2 h, and then cooling it to room temperature;
[0118] 7) After the activation is completed, the reaction conditions are changed, and a mixed atmosphere of nitrogen and carbon monoxide is selected to further carry out the self-growth process of the calcium source on the fiber membrane surface and carbonization treatment, wherein the carbon monoxide gas flow rate is 10 mL / min, and the temperature is increased to 800°C at a heating rate of 5°C / min, and the total gas flow rate is maintained at 100 mL / min. After the constant temperature is maintained for 1 hour, it is naturally cooled to room temperature, and finally a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane is obtained.
[0119] The obtained calcium self-grown lignin-based carbon capture electrospun nanofiber membrane was tested for carbon dioxide adsorption performance. The sample was placed in a tubular furnace and heated to 500°C at a rate of 10°C / min under nitrogen conditions. It was pretreated at this temperature for 3 hours to completely remove excess moisture and gas to ensure the accuracy of the test results; the carbon dioxide adsorption capacity was 2.16mmol / g when the adsorption was performed at a set adsorption temperature of 140°C, an adsorption time of 90 minutes, and nitrogen and carbon dioxide gas flow rates of 200mL / min and 3mL / min, respectively.
[0120] Comparative Example 1
[0121] The difference from Example 1 is that no soluble calcium source is added during the preparation of the lignin-based carbon capture electrospun nanofibers.
[0122] The obtained calcium-free self-grown lignin-based carbon capture electrospun nanofiber membrane was tested for carbon dioxide adsorption performance. The sample was placed in a tubular furnace and heated to 500°C at a rate of 10°C / min under nitrogen conditions. It was pretreated at this temperature for 3 hours to completely remove excess moisture and gas to ensure the accuracy of the test results; the carbon dioxide adsorption capacity was 1.13mmol / g when the adsorption was performed under the conditions of setting the adsorption temperature to 140°C, the adsorption time to 90min, and the nitrogen and carbon dioxide gas flow rates to 200mL / min and 3mL / min respectively.
[0123] Summary: By comparing the carbon dioxide adsorption of the carbon capture electrospun nanofiber membrane prepared in the above Example 1 and Comparative Example 1, it can be seen that the adsorption amount of Example 1 is more than twice that of Comparative Example 1, which has a significant carbon adsorption effect.
[0124] Comparative Example 2
[0125] The difference from Example 1 is that during the carbonization process of the lignin-based carbon capture electrospun nanofiber preparation, a pure nitrogen atmosphere is selected. Other conditions are the same as those of Example 1.
[0126] The carbon dioxide adsorption performance of the lignin-based carbon capture electrospun nanofiber membrane prepared in this comparative example was tested. The sample was pretreated in a nitrogen atmosphere at 500°C to completely remove excess moisture and gas therein to ensure the accuracy of the test results; the carbon dioxide adsorption amount was 1.78mmol / g when the adsorption was performed under the conditions of setting the adsorption temperature to 140°C, the adsorption time to 90min, and the nitrogen and carbon dioxide gas flow rates to 200mL / min and 3mL / min respectively.
[0127] Summary: By comparing the adsorption amount of carbon dioxide by the carbon capture electrospun nanofiber membrane prepared in the above Example 1 and Comparative Example 2, it can be known that the carbon dioxide capture performance of the nanofiber membrane is effectively improved after carbonization treatment under mixed atmosphere conditions in Example 1. This is because at high temperature, carbon monoxide easily undergoes etching reaction with the components in the nanocarbon fiber matrix to generate volatile products, which helps to form pores on the fiber surface and increases the specific surface area of the adsorbent.
[0128] Figure 1 This is the X-ray diffraction spectrum of the calcium self-grown lignin-based carbon capture electrospun nanofiber membrane prepared in Example 1 of the present invention; it can be seen from the figure that the components of the carbon nanofiber are mainly graphite carbon and calcium sulfide, indicating that the calcium source is successfully constructed into the carbon nanofiber using the above technology;
[0129] Figure 2This is a microscopic morphology of the calcium self-grown lignin-based carbon capture electrospun nanofiber membrane prepared in Example 1 of the present invention; it can be seen from the figure that abundant and uniform calcium source particles are distributed on the surface of the carbon nanofiber, and combined with the XRD spectrum, it is found that the calcium source particles exist in the form of calcium sulfide, indicating that the above preparation method can fully utilize the sulfur component of lignin to combine it with the calcium source, and evenly distribute it on the fiber surface;
[0130] Figure 3 This is a physical picture of the calcium self-grown lignin-based carbon capture electrospun nanofiber membrane prepared in Example 1 of the present invention; it can be seen from the figure that the carbon nanofiber membrane prepared by this technology has excellent flexibility and ductility, which provides excellent application conditions for its large-scale application in the field of carbon capture;
[0131] Figure 4 This is a pore size distribution diagram of the calcium self-grown lignin-based carbon capture electrospun nanofiber membrane prepared in Example 1 of the present invention; it can be seen from the figure that the carbon nanofiber membrane prepared by the present invention has a rich pore size structure.
[0132] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane, characterized in that: The calcium source, lignin and spinning aid solution are mixed and treated in a water bath to obtain a uniform spinning precursor solution; and then subjected to electrospinning and carbonization treatment to prepare a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane; The lignin content in the spinning precursor solution is 5 to 20 wt %; the amount of calcium source added is 5 to 60% of the lignin quality; The calcium source includes one or more of calcium chloride dihydrate, calcium formate, calcium acetate, calcium nitrate tetrahydrate and calcium hydroxide.
2. The method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane according to claim 1, characterized in that: The spinning aid solution is obtained by uniformly mixing a high molecular polymer and a polar solvent in a mass volume ratio of 1 g: (5-20) mL.
3. The method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane according to claim 2, characterized in that: The high molecular polymer includes one or more of polyacrylonitrile, polyacrylonitrile copolymer, polyether sulfone, polylactic acid, polyvinyl alcohol, polyoxyethylene, polyvinylidene fluoride and polyvinyl pyrrolidone; The polar solvent includes one or more of N,N dimethylformamide, N,N dimethylacetamide, acetone, dichloromethane, dimethyl sulfoxide, and acetic acid.
4. The method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane according to claim 1, characterized in that: The parameters in the electrospinning process are: The distance between the syringe needle and the receiving device is controlled to be 15 to 20 cm, the applied voltage is 10 kV to 25 kV, the advancement rate is 0.02 to 1.0 mm / min, and the receiver rotation speed is 100 to 500 rpm.
5. The method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane according to claim 1, characterized in that: The carbonization process is carried out in a mixed gas atmosphere of carbon monoxide and nitrogen; The carbon monoxide accounts for 5-30% of the mixed gas flow rate, and the flow rate of the mixed gas is 80-260 mL / min.
6. The method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane according to claim 1, characterized in that: The temperature during the carbonization process is: Raise the temperature from room temperature to 600-900°C and maintain at 600-900°C for 1-3 hours.
7. The method for preparing a calcium self-grown lignin-based carbon capture electrospun nanofiber membrane according to claim 6, characterized in that: The heating rate is 3-10°C / min.
8. A calcium self-grown lignin-based carbon capture electrospun nanofiber membrane, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method and application of ionic liquid functionalized polyacrylonitrile nanofiber membrane
CN109647359A
Application of electrostatic spinning nanofiber membrane in gas adsorption
CN115945023A
Lignin carbon nanofiber and preparation method thereof
CN101768799A
Metal organic framework / carbon nanofiber composite membrane material and preparation method thereof
CN107201645A